ISSUES OF SPEECH DEVELOPMENT OF STUDENTS - Shadiyeva Dilfuza Urinbayevna (Web of Journals Publishing, 2023)
The article describes the issues of teaching pupils’ speech in the mother tongue lessons of primary grades, where education is conducted in Uzbek languages.
Keywords: new words, grammatical devices, speech skills, unfamiliar morphological forms, syntactic devices, language phenomena.